Pengaruh Penerapan Metode Suggestopedia terhadap Penguasaan Kosakata Bahasa Arab Siswa di Kota Pekanbaru - Akbar, Syawal Rizki; Wahyudi, Hakmi; Azhar, Muhammad (Lembaga Swadaya Masyarakat Asosiasi Masyarakat Madani Indonesia (AMMI), 2024)
Education plays a central role in shaping a quality generation and realizing the integrity of a nation. In the context of Arabic language education in Indonesia, especially at MI Tahfizh Cendekia Kota Pekanbaru, challenges related to the mastery of Arabic vocabulary have become a primary concern. This research aims to explore the significant impact of the implementation of the Suggestopedia method on the mastery of Arabic vocabulary among students at MI Tahfizh Cendekia Pekanbaru. Using a quantitative approach with a quasi-experimental research design, this study involved students from classes III A and III B as research subjects. The Suggestopedia method was applied to the experimental group, while the control group followed conventional methods. Data analysis using t-tests and N-Gain tests revealed a significant difference between the two groups, with the experimental group showing a greater improvement in vocabulary mastery. The post-test results indicated that the Suggestopedia method effectively enhanced the mastery of Arabic vocabulary among students, with all students in the experimental group achieving an Excellent category. Although the control group also achieved positive results, the experimental group demonstrated a greater improvement. These findings contribute significantly to the implementation of the Suggestopedia method as an innovative strategy in enhancing Arabic vocabulary mastery in the context of MI education.